2017
DOI: 10.1038/s41598-017-02905-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA from human plasma and serum differs in content of telomeric sequences and its ability to promote immune response

Abstract: Circulating cell-free DNA (cfDNA) may be involved in immune response regulation. We studied the variations in abundance of telomeric sequences in plasma and serum in young healthy volunteers and the ability of cfDNA contained in these samples to co-activate the TNF-α m RNA expression in monocytes. We performed qPCR to determine relative telomere length (T/S ratios) in plasma, serum and whole blood of 36 volunteers. Using paired samples of plasma and serum and DNase treatment, we analysed the contribution of cf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
(48 reference statements)
0
29
0
2
Order By: Relevance
“…Currently, it is still widely discussed, if cfDNA should be extracted from serum or plasma. Some studies discovered that the level of cfDNA was higher in serum compared to plasma [12]; because a part of cfDNA is released during blood cell lysis in the clotting process in tubes before centrifugation, which leads to contamination [13]. Thus, plasma is the preferable biological sample in most studies.…”
Section: Storage and Detection Methods For Cfdnamentioning
confidence: 99%
“…Currently, it is still widely discussed, if cfDNA should be extracted from serum or plasma. Some studies discovered that the level of cfDNA was higher in serum compared to plasma [12]; because a part of cfDNA is released during blood cell lysis in the clotting process in tubes before centrifugation, which leads to contamination [13]. Thus, plasma is the preferable biological sample in most studies.…”
Section: Storage and Detection Methods For Cfdnamentioning
confidence: 99%
“…Increasing evidences suggested that it might be passively released by apoptotic and necrotic cells as DNA fragments (24) or actively excreted from distant tumor cells for signal transmission (25). The higher amount of cfDNA was reported from serum compared to plasma (26). Our study found increased concentration of cfDNA in serum within 5 years ahead of clinical diagnosis of GC (data not shown).…”
Section: Figure 2 |mentioning
confidence: 45%
“…We went on to demonstrate that HOLMES could maintain highconcentration performance in clinical samples and enable the detection of ultralow-abundance molecular biomarkers. In clinical samples, the much more abundant cell-free DNAs [e.g., ∼100 ng/mL in human serum (33)] and proteins [e.g., ∼100 mg/mL in human serum (34)] would present significant noises for the sensitive and specific detection of targets and also suppress the concentration of targets (SI Appendix, section 8). HOLMES uses affinity probes to recognize the targets and modulate their electrophoretic mobility, which enables the selective enrichment of targets and simultaneous depletion of interfering background biomolecules.…”
Section: Nucleic Acid Detection By Holmesmentioning
confidence: 99%